Multi-objective optimisation of tribological parameters of AMCs (356/fly ash). (2022) - Udaya Prakash, J.; Divya Sadhana, A.; Jebarose Juliyana, S; Ananth, S; Sarala Rubi, C.
Abstract: Today's industries are looking for materials that are less expensive and have a higher strength-to-weight ratio. Researchers have been driven to produce materials with superior mechanical and tribological properties as part of the global quest for sustainable development. In terms of wear resistance, AMCs beat their monolithic counterparts that are not reinforced. Stir casting was used to create Aluminium Matrix Composites made of 356 aluminium alloy with particulate fly ash reinforcements weighing 3 percent, 6 percent, and 9 percent. A pin-on-disc machine was used to conduct the wear test, which followed ASTM Standard G99-05 guidelines. The goal of this study is to explore the effects of sliding speed, load, sliding distance, and reinforcing weight percentage on coefficient of friction and specific wear rate using Grey Relational Analysis (GRA) and ANOVA. By using GRA, the tribological behaviour of composites has been predicted successfully.